A molecular deletion of distal chromosome 4p in two families with a satellited chromosome 4 lacking the Wolf-Hirschhorn syndrome phenotype. - Estabrooks, L L (1992)
We report two families with a satellited chromosome 4 short arm (4ps). Satellites and stalks normally occur on the short arms of acrocentric chromosomes; however, the literature cites several reports of satellited nonacrocentric chromosomes, which presumably result from a translocation with an acrocentric chromosome. This is the first report of 4ps chromosomes. Our families are remarkable in that both unaffected and affected individuals carry the 4ps chromosome. The phenotypes observed in affected individuals, although dissimilar, were sufficient to encourage a search for a deletion of chromosome 4p. By Southern blot analysis and fluorescence in situ hybridization, a deletion of material mapping approximately 150 kb from chromosome 4pter was discovered. This deletion is notable because it does not result in the Wolf-Hirschhorn syndrome and can result in an apparently normal phenotype. We speculate that homology between subterminal repeat sequences on 4p and sequences on the acrocentric short arms may explain the origin of the rearrangement and that position effect may play a role in the expression of the abnormal phenotype.